School-tripped - Holm, Jennifer L.; Holm, Matthew (Holm, Jennifer L. Babymouse. Tales from the locker, 2019)
When Babymouse's art class goes on a field trip to the museum in the big city, she decides to test her freedom by exploring the city without a chaperone.